Multi-Criteria Analysis Techniques to Assess the Efficiency of Using Blockchain in Logistics - Azimov, Dilmurod; Stoyanova-Asenova, Stanislava; Petrova, Mariana; Asenov, Anatoliy (Dr. Viktor Koval, 2024)
Introduction. In complex areas of supply chain management and logistics, there is a need to use innovative solutions to improve economic efficiency, which is particularly important in the context of evolving digital technologies. The solution to the supply chain management problem is based on the use of multicriteria analysis methods to assess the efficiency of implementing modern information technologies in purchase procedures, such as blockchain technology, on the flexibility of the supply chain. Aim and tasks. The study aims to examine the effects of blockchain to the adaptability of supply chains, its transparency, and the trust levels among its participants. Results. The developed multi-criteria analysis tool provides the ability to specify weighting coefficients individually for each of the evaluated criteria, making it possible to consider a particular company's priorities within the framework of the optimised process. A survey of experts who knew the subject area under study was conducted to obtain the data necessary for analysis. This can provide expert opinions to assess the feasibility of certain alternatives when making decisions. The assessment conducted by experts revealed three main effects of blockchain and smart contracts on business: increasing the reliability of stored information, increasing the integrity of stored information, and integrating various information flows into a single information system. Conclusions. The developed multi-criteria analysis tool allows for the specification of weighting factors, or “preferences”, for each of the examined criteria. This feature allows for considering a company’s priorities within the context of the process being improved. Blockchain and smart contracts offer key benefits in streamlining logistics procedures, primarily by bolstering the trust and dependability of the data storage system by creating local copies of data for each participant in the chain and improving data quality by integrating data from various sources into a single blockchain platform. In addition, it increases data security and minimises the risk of falsification because of the impossibility of making unauthorised changes to the database (at the current stage of system development) and the high degree of information integrity ensured by its distributed storage.